A systematic study on Endotribelos Grodhaus (Diptera: Chironomidae) from Brazil including DNA barcoding to link males and females - Trivinho-Strixino, Susana; Pepinelli, Mateus (Zootaxa, 2015)
Six new species of Endotribelos from Brazil are described and illustrated as male, female, pupa and larva: E. bicolor sp. n., E. fulvidus sp. n., E. jaragua sp. n., E. jiboia sp. n., E. semibruneus sp. n. and E. sublettei sp. n. The female of E. calophylli Roque & Trivinho-Strixino and the larvae of four unknown morphotypes are also described. Keys including males and larvae of all known species of Endotribelos are provided. Adults’ males and females from five species were linked using DNA Barcoding mtCOI sequences.